Contingent Factors Affecting the Financial Performance of Manufacturing Companies: The Case of East Java, Indonesia - Hariyati, Hariyati; Tjahjadi, Bambang (Asian Journal of Business and Accounting, 2018)
Manuscript type: Research paper. Research aims: This study aims to examine how contextual variables which include innovation strategy, management accounting infor- mation system and internal business process performance affect the financial performance of manufacturing companies in East Java, Indonesia. Design/ Methodology/ Approach: This study employs a quantitative approach to explain the relationship among the variables. The data of 135 managers were collected and then analysed through the partial least squares (PLS) approach. Research findings: Results show that management accounting infor- mation system and business process performance partially mediate the innovation strategy-financial performance relationship. Theoretical contributions/ Originality: This study expands on pre- vious works by investigating the roles of management accounting information system and internal business process performance as mediating variables between innovation strategy and firm’s financial performance. Practitioner/ Policy implications: This study provides insights into how management accounting information system and internal busi- ness process performance impact innovation strategy and financial performance. The results imply that managers need to improve the design and implementation of their accounting system and their internal business process performance. This initiative can support the firm’s innovation strategy which impacts on the firm’s financial performance. The implications drawn from this study justify two things: (1) firms need to be more proactive in their product and process innovations so as to remain competitive in the global market; and (2) managers need to develop intangible assets such as a management accounting information system in the era of knowledge economy. Research limitation: This study focusses on the manufacturing companies of the East Java Province of Indonesia therefore, general- isability of the findings may be restricted. Future studies need to incorporate larger and more diverse samples. This study did not consider the companies’ business life cycle hence, the full impact of the firms’ financial performance may not have been captured. Keywords: Financial Performance, Innovation Strategy, Internal Business Process Performance, Management Accounting Information System. JEL Classification: M41